A COMPUTER ENGINEERING APPROACH TO MITIGATING BLIND SPOTS CAUSED BY COVERAGE DEFICIENCY IN WIRELESS NETWORKS - Eenas Suwayd; Nizar Ramadan; Adnan Alrammash (Surman Journal of Science and Technology, 2026)
Wireless ad hoc networks consist of a collection of mobile wireless nodes that cooperate to establish communication without relying on fixed infrastructure or centralized administration. In such networks, each node can function as a transmitter, receiver, or intermediate relay. Despite their flexibility and ease of deployment, wireless networks are vulnerable to several challenges arising from their decentralized architecture and reliance on wireless communication channels. One of the most significant issues is the occurrence of blind spots, which are regions experiencing weak or no signal coverage, leading to communication degradation and reduced network performance. This study aims to investigate the characteristics of wireless ad hoc networks, identify the causes and effects of coverage blind spots, and propose possible solutions to mitigate their impact. MATLAB was employed as a simulation platform to model wireless network behavior and analyze signal distribution within the coverage area. The simulation results revealed the existence of regions with significant signal attenuation, influenced by factors such as node locations, propagation characteristics, and environmental conditions. Furthermore, the study demonstrated that optimizing node placement and improving coverage strategies can effectively reduce blind spots and enhance overall network performance.